PERAN SUSTAINABILITY REPORTING DALAM MENDUKUNG NET ZERO EMISSION: TANTANGAN, PELUANG, DAN STRATEGI MITIGASI - Komang Trisna Ayu Laskari; Agus Bandiyono (Jurnal Riset Akuntansi, 2025)
The issue of environmental change has become a global concern due to its increasingly real impact on ecosystems, health, and the world economy. Global warming and increasing greenhouse gas emissions require mitigation efforts from various parties, including the industrial sector and companies. This study aims to analyze the role of Sustainability Reporting (SR) in supporting the achievement of Net Zero Emission and explore the challenges, opportunities, and recommendations that can improve the quality of sustainability reporting in companies. Using a scoping review, this study examines 17 literature articles that discuss the role, challenges, opportunities, and strategies for mitigating climate change through the implementation of Sustainability Reporting. The results of the study indicate that sustainability reporting has an important role in supporting the global commitment to net zero emissions. However, there are challenges that need to be faced such as reporting standardization, limited resources, and data subjectivity in the reporting. This study also identifies opportunities to improve the quality of SR through integration with business strategies, utilization of advanced technologies such as blockchain and AI, and collaboration between stakeholders. The recommendations provided include more specific reporting standards, comprehensive emission measurements, and independent verification to support the achievement of Net Zero Emission.